Oxford Bible atlas - Curtis, Adrian; May, Herbert G. (Herbert Gordon), 1904-1977. (Oxford ; New York : Oxford University Press, 2007)
"The Oxford Bible Atlas provides a superb guide to the lands in which the Bible's stories are set, from Genesis to Revelation. This new edition of the best-selling Atlas has been thoroughly revised to bring it up to date with the latest insights from biblical scholarship, archaeology, and topography. It now includes full-colour maps and illustrations throughout."--BOOK JACKET.
The setting. The text in context ; The lands of the BIble ; Climate, flora, and fauna ; Israel and the nations -- The Hebrew Bible. The setting of the Genesis stories ; The patriarchs in Canaan ; The exodus and wilderness traditions ; The stories of Joshua and the Judges, Samuel and Saul ; The stories of David and Solomon ; Ancient trade routes ; The kingdoms of Israel and Judah ; The Assyrian Empire ; The kingdom of Judah ; The Babylonian Empire ; The Persian Empire ; Judah, Yehud, and Judea ; Alexander's Empire and its aftermath: the Hellenistic Period ; Jerusalem in the 1st millennium BCE -- The New Testament. The kingdom of Herod and his successors ; The ministry of Jesus and the beginnings of the church ; The Roman Empire: the background of the New Testament ; Jerusalem in New Testament times ; Paul's journeys ; The cradle of Christianity -- Archaeology in Bible lands. Archaeology in the ancient Near East ; Archaeology and the Bible.
Previous ed.: edited by Herbert May. 1984.
Includes bibliographical references (p. 203) and indexes.
Keywords: Bible -- Geography; Bible -- Geography -- Maps